EXPLORING THE MOTIVATIONAL TEACHING PRACTICES IN ENGLISH INTENSIVE PROGRAM AT AN INDONESIAN ISLAMIC UNIVERSITY - Hustiana, Hustiana (English Language, Linguistics, and Culture International Journal, 2021)
The  aim of this research was to explore the application of motivational teaching practices used by instructors and their impact on the students’ motivation. The researcher applied case study that conducted in English Intensive Program of UIN Alauddin Makassar namely Pengembangan Intesifikasi Bahasa Asing (PIBA) in academic year 2017/2018. The data sources were 2 instructors and 72 first semester students that taken through purposive sampling. The first instructor taught Guidance and Counseling C Department students that consisted of 30 students and the second instructor taught Nursing A Department students that consisted of 32 students. In collecting data, the motivational teaching Practices by instructor was taken through interview and observation. While, the impact of the application of motivational teaching practices on the students’ motivation was taken through questionnaire. In brief, it could be concluded that there were two kinds instructors’ perception about motivational teaching practices, they were Strongly Motivating Instructor (SMI) and Weakly Motivating Instructor (WMI). Besides, there were two kinds of instructors’ motivation teaching practices implementation, they were Highly Implemented Motivational Teaching Practices (HIMTP) and Lowly Implemented Motivational Teaching Practices (LIMTP). Thus, the impact on the students’ motivation was also different. The Strongly motivating instructor who implemented motivational teaching practices highly had more self-confidence students in learning English. While, the weakly motivating instructor who implemented motivational teaching practices lowly had less self-confidence students in learning English. Even though it could not be denied that all of the students from both classes still had high anxiety and low intrinsic motivation. Therefore, it was suggested for the Instructor to applied personal approach to decrease the anxiety of the students and to increase their satisfying in learning English.